Membrane Tension in Swelling and Shrinking Molluscan Neurons - Dai, Jianwu (J Neurosci, 1998)
When neurons undergo dramatic shape and volume changes, how is surface area adjusted appropriately? The membrane tension hypothesis—namely that high tensions favor recruitment of membrane to the surface whereas low tensions favor retrieval—provides a simple conceptual framework for surface area homeostasis. With membrane tension and area in a feedback loop, tension extremes may be averted even during excessive mechanical load variations. We tested this by measuring apparent membrane tension of swelling and shrinkingLymnaea neurons. With hypotonic medium (50%), tension that was calculated from membrane tether forces increased from 0.04 to as much as 0.4 mN/m, although at steady state, swollen-cell tension (0.12 mN/m) exceeded controls only threefold. On reshrinking in isotonic medium, tension reduced to 0.02 mN/m, and at the substratum, membrane invaginated, creating transient vacuole-like dilations. Swelling increased membrane tension with or without BAPTA chelating cytoplasmic Ca(2+), but with BAPTA, unmeasurably large (although not lytic) tension surges occurred in approximately two-thirds of neurons. Furthermore, in unarborized neurons voltage-clamped by perforated-patch in 50% medium, membrane capacitance increased 8%, which is indicative of increasing membrane area. The relatively damped swelling–tension responses ofLymnaea neurons (no BAPTA) were consistent with feedback regulation. BAPTA did not alter resting membrane tension, but the large surges during swelling of BAPTA-loaded neurons demonstrated that 50% medium was inherently treacherous and that tension regulation was impaired by subnormal cytoplasmic [Ca(2+)]. However, neurons did survive tension surges in the absence of Ca(2+) signaling. The mechanism to avoid high-tension rupture may be the direct tension-driven recruitment of membrane stores.